The impact of contextual bias on novice examiners in firearms examinations and fingerprints analyses - Derakhshan, Melissa (My University, 2024)
Despite efforts to maintain objectivity in analysis and interpretations, bias and human error still impact forensic science. Diversity in the perspectives, ideologies, techniques, and experience of forensic scientists generates a lack of standardized systems and methodologies in the analysis of evidence and introduces bias into forensic science. This leads to complications regarding interpretation and can result in subjectivity being introduced into testimony. The literature discusses the importance of comprehending bias as a whole and its impact on various fields in forensic science. The use of subjective judgments can substantially influence the analysis of fingerprints, firearms, pathology, bite marks, and crime scenes. Subjectivity can occur due to previous contextual information being given to an individual prior to examination. Objective analysis is crucial for factual investigations and to prevent wrongful convictions. This study focuses on DNA contextual information and how it impacts the conclusions of novice analysts when analyzing firearms and fingerprints. In this study, twenty-one participants from a forensic science analysis lab course conducted bullet comparisons and eighteen participants from an advanced fingerprint course analyzed fingerprints. A randomly assigned between-subject Fisher's exact test was used to analyze the data. In the examination of both fingerprints and firearms, participants were given contextual information regarding a crime scene, a suspect in custody, and whether DNA found at the scene matched, did not match, or was unknown to be a match to the suspect. Fingerprint novices were then asked to analyze and compare an unknown fingerprint from the crime scene to one of the suspects known prints and firearms novices were asked to compare a bullet collected from the crime scene to a bullet fired from the suspect's weapon. Examiners were also asked to indicate their level of confidence in their conclusions. Results indicated that when novices were not provided contextual DNA information, they formed conclusions with 100% accuracy in both fingerprints and firearms examinations. Statistical analysis indicated that for the fingerprint task, there was no significant difference in the proportions of correct answers for all groups and no significant differences in the median confidence levels of participants in different groups. For the firearms task, there was also no significant difference in the proportions of correct answers for all groups. However, confidence levels for novices in the firearms task were significantly higher when no contextual DNA information was provided. In both fingerprints and firearms, participants had 100% accuracy in the conclusion when analyzing prints or bullets in the control group vs. lower percentages of accuracy in the experimental group in which participants were provided with DNA contextual information.
Keywords: Forensic scientists; Decision making; Context effects (Psychology); Bullets--Identification; Fingerprints--Identification; Contextual bias; Firearms examination; Fingerprint analysis